2019
DOI: 10.1186/s12943-019-1088-x
|View full text |Cite
|
Sign up to set email alerts
|

m6A modification suppresses ocular melanoma through modulating HINT2 mRNA translation

Abstract: Background: Dynamic N 6-methyladenosine (m 6 A) RNA modification generated and erased by N 6methyltransferases and demethylases regulates gene expression, alternative splicing and cell fate. Ocular melanoma, comprising uveal melanoma (UM) and conjunctival melanoma (CM), is the most common primary eye tumor in adults and the 2nd most common melanoma. However, the functional role of m 6 A modification in ocular melanoma remains unclear. Methods: m 6 A assays and survival analysis were used to explore decreased g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
187
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(194 citation statements)
references
References 72 publications
7
187
0
Order By: Relevance
“…In melanoma, depletion of YTHDF2 accelerated cell proliferation and migration by strikingly upregulating the mRNA levels of three key intrinsic pro-tumorigenic factors, including PD-1 (PDCD1), CXCR4, and SOX10, which was dependent on a reduced m 6 A-mediated mRNA decay [64]. Furthermore, YTHDF1 promoted the translation of tumor suppressor HINT2 mRNA which was methylated by m 6 A, thus playing a repressive role in ocular melanoma [65].…”
Section: Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…In melanoma, depletion of YTHDF2 accelerated cell proliferation and migration by strikingly upregulating the mRNA levels of three key intrinsic pro-tumorigenic factors, including PD-1 (PDCD1), CXCR4, and SOX10, which was dependent on a reduced m 6 A-mediated mRNA decay [64]. Furthermore, YTHDF1 promoted the translation of tumor suppressor HINT2 mRNA which was methylated by m 6 A, thus playing a repressive role in ocular melanoma [65].…”
Section: Melanomamentioning
confidence: 99%
“…Downregulating the mRNA and protein levels of three key intrinsic pro-tumorigenic factors, including PD-1 (PDCD1), CXCR4 and SOX10 [64] YTHDF1 HINT2 Promoting the translation of HINT2 mRNA [65] Breast cancer YTHDF2 BNIP3 Facilitating the degradation of BNIP3 mRNA [66] Pancreatic cancer IGF2BP2 DANCR Enhancing the DANCR expression [67] Acute myeloid leukemia…”
Section: Itga6mentioning
confidence: 99%
“…On the other hand, in ocular melanoma, YTHDF1 promotes the translation of m 6 A-containing HINT2 mRNA, a tumor suppressor (65). Scientists reported decreased m 6 A levels in these tumor samples, which was significantly correlated with tumor progression both in vitro and in vivo.…”
Section: Alkbh5mentioning
confidence: 99%
“…With the help of YTHDF1, the translation of methylated HINT2 mRNA, a tumour suppressor of ocular melanoma, was significantly accelerated, meaning m 6 A modification obviously inhibits the progression of ocular melanoma. Moreover, investigation of ocular melanoma samples indicated that decreased m 6 A levels were highly associated with poor prognosis [140].…”
Section: Regulatory Roles Of Rna Modifications In Pathogenesis Aberramentioning
confidence: 99%